My father, myself, and my muscles: Associations between muscle dysmorphia, narcissism and relationship with father among exercising males. (June 2023) - Boulter, Matt W.; Wooldridge, Tom; Bjelland, Vegard E.; Sandgren, Sebastian S.
Abstract: Research has yet to examine the associations between muscle dysmorphia (MD), narcissism and relationship with father in a male population. This study aimed to address this. We hypothesized that a negatively experienced relationship with the father for males will lead to an increase in MD symptoms due to undermined self-esteem that stems from a lack of the father as a positive masculine role model. A total of 503 exercising males ( M age = 28.5, SD = 9.6 years) completed self-report measures of MD, narcissism, and relationship with father. Our hypothesized indirect effect model found a negative indirect effect of relationship with father on MD symptoms via vulnerable narcissism, but not via grandiose narcissism. Analysis of individual path coefficients also revealed that a poor relationship with father impacts the development of vulnerable narcissism, but not grandiose narcissism. These findings alert practitioners to the fact that some individuals' MD symptoms may be an attempt to protect the fragile self-esteem central to vulnerable narcissism. Practitioners should consider exploring individuals' feelings and perceptions about their fathers in the treatment of MD. Moreover, future research should build on these findings and explore the observed associations in a longitudinal design to assess the causal model. Highlights: Father absence is related to increased muscle dysmorphia symptoms in males. This can be explained through the development of vulnerable narcissism. Father-son relationship may be an important aspect in muscle dysmorphia treatment. Future longitudinal research is needed to confirm the findings.